A Typology of Ethical Issues to Better Support the Development of Ethical Sensitivity Among Healthcare Professionals - Drolet, Marie-Josée (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
For many healthcare professionals, identifying the ethical issues arising from their professional practice can be a challenge, for a variety of reasons. This paper presents a typology of six different types of ethical issues that can support the development of healthcare professionals’ ethical sensitivity, i.e., their ability to identify ethical issues encountered in their day-to-day practice. In addition to defining each of these issues, i.e., ethical blindness, myopia, dilemma, temptation, silence, and distress, examples are given and possible solutions proposed.